Isometric weight training: Its effects on the development of muscular function and the endocrine system over an 8-week training period - Giorgi, A.; Wilson, G. J.; Weatherby, R. P.; Murphy, A. J. (The Journal of Strength and Conditioning Research, 1998)
This study examined the comparative effects of functional isometric (FI) and heavy weight (HW) training on the development of strength and power together with specific hormonal adaptations in experienced athletes. Thirty three subjects were randomly divided into 3 groups: Fl weight training, HW, and Control. Both the FI and HW completed an 8-week training cycle involving 2 sessions a week. All subjects were tested on the following measures: 1-RM (repetition maximum) bench press; 1-RM squat; 40-m sprint; countermovement jump (CMJ); stretch-shorten cycle (SSC); and concentric push-up. Urinary concentrations of testosterone (T), cortisol (C), and luteinizing hormone (LH) were assessed via liquid chromatography, and immunoassay techniques and ratios were used to determine the anabolic or catabolic response to the different training methods. Both FI and HW training significantly increased muscular strength. Furthermore, the HW group significantly improved in the CMJ compared to the control group. Among the stronger subjects, Fl resulted in greater improvements in upper body SSC movements compared to the HW training. Urinary concentrations of T, C, LH, as well as the hormone ratios, were unaffected by either training modality.